Mass spectrometry-based metabolomics approach for metabolite profiling and biomarker discovery of Acanthaceae medicinal plants and tissue cultures - Cheong, Bo Eng; How, Siew Eng; Yong, Wilson Thau Lym (Universiti Malaysia Sabah, 2012)
Clinacanthus nutans (Sabah Snake Grass) and Strobilanthes crispus {daun pecah beling) from the family of Acanthaceae, are gaining research interest as the plants have been reported to possess various bioactivities. The present study was aimed to profile and identify the biomarker compounds of C. nutans and S. crispus plants and its tissue cultures using GCMS-based metabolomics approach. Using this high-throughput instrument coupled with advanced chemoinformatics softwares, the plants were found to rich with squalene, pentacyclic triterpenoids such as lupeol, betulin, phytosterols such as stigmasterol, campesterol and others such as alphatocopherol, didecan-2-yl phthalate, beta-tocopherol. As the metabolomes of C. nutans and S. crispus unfold, it is believed that such information will play critical role in the standardization and development of herbal drugs derived from the plants in the future.